2019
DOI: 10.1161/circoutcomes.119.005597
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors and Myocardial Infarction in the Transgender Population

Abstract: Background: As of 2016, ≈1.4 million people in the United States identify as transgender. Despite their growing number and increasing specific medical needs, there has been a lack of research on cardiovascular disease (CVD) and CVD risk factors in this population. Recent studies have reported that the transgender population had a significantly higher rate of CVD risk factors without a significant increase in overall CVD morbidity and mortality. These studies are limited by their small sample sizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
134
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(143 citation statements)
references
References 23 publications
2
134
1
2
Order By: Relevance
“…Multiple previous studies have shown no association between hormone treatment and CVD for transmen, 6,12,22,23,25 consistent with our findings; a recent study did find an increase risk for selfreported CVD among transmen, although this was not attributed specifically to hormone use. 33 There are important limitations to this study. The analysis was observational in nature and clinicians may have prescribed certain hormones based on their patients' CVD risk, which we are unable to control for; likewise, hormone concentrations were available when tests were ordered by clinicians, and may have been more common when there were clinical concerns.…”
Section: Discussionmentioning
confidence: 94%
“…Multiple previous studies have shown no association between hormone treatment and CVD for transmen, 6,12,22,23,25 consistent with our findings; a recent study did find an increase risk for selfreported CVD among transmen, although this was not attributed specifically to hormone use. 33 There are important limitations to this study. The analysis was observational in nature and clinicians may have prescribed certain hormones based on their patients' CVD risk, which we are unable to control for; likewise, hormone concentrations were available when tests were ordered by clinicians, and may have been more common when there were clinical concerns.…”
Section: Discussionmentioning
confidence: 94%
“…Transgender women also had higher odds of diabetes and cardiovascular disease compared with cisgender men and cisgender women. Recent studies that examined transgender individuals' health irrespective of cancer did not report elevated rates of diabetes, but did demonstrate elevated cardiovascular disease in transgender men and transgender women. Although additional studies, including longitudinal studies, of transgender cancer survivors' health behaviors and health are needed, clinicians need to be aware of the likely more complex medical care needs of transgender men and transgender women with cancer, given their poor physical health, especially their comorbid diabetes and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjusting for age, diabetes mellitus, chronic kidney disease, smoking, hypertension, hypercholesterolemia, and exercise, transgendered women only had a significantly increased risk of MI compared to cisgendered females (odds ratio [OR], 2.56; 95% CI: 1.78–3.68; p < 0.01) but not cisgendered men. 12…”
Section: Cardiovascular Outcomes In Transgendered Peoplementioning
confidence: 99%
“…After adjustment for cardiovascular risk factors, however, the study demonstrated that transgendered men had an increased risk for MI compared to both cisgendered populations (OR 2.53 95% CI: 1.14–5.63 compared to cisgendered men; OR 4.90 95% CI: 2.21–10.90 compared to cisgendered women). 12…”
Section: Cardiovascular Outcomes In Transgendered Peoplementioning
confidence: 99%